2000
DOI: 10.1191/146342300674617169
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions of changing professional boundaries and the future of ‘nurse-led’ services

Abstract: Nurses are increasingly being employed instead of doctors in some areas of work. This article examines this phenomenon in relation to a 'nurse-led' Personal Medical Services Primary Care Act pilot scheme. As part of an evaluative project, we examined the way in which patients understood and constructed nursing roles in the context of their use of primary care services in a socially deprived area. Whilst professional roles are established to some extent as the result of negotiation between and within profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…People’s perceptions of a nurse‐led service may change when they have actually experienced this new form of health‐care. A recent study has shown that people living in a highly deprived area were most enthusiastic about their nurse‐led practice once they had experienced the service for a few months 26 …”
Section: The Results Of the Semi‐structured Interviewsmentioning
confidence: 99%
“…People’s perceptions of a nurse‐led service may change when they have actually experienced this new form of health‐care. A recent study has shown that people living in a highly deprived area were most enthusiastic about their nurse‐led practice once they had experienced the service for a few months 26 …”
Section: The Results Of the Semi‐structured Interviewsmentioning
confidence: 99%
“…Chapple et al [4] carried out a case study which was an attempt to evaluate clients' perceptions of changing professional boundaries in primary care services. The results showed that some patients credited the leading nurse as the most highly qualified and perceived the nurse to be a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives regard primary care services as a broader public health resource besides a means of simply providing treatment to individuals. A recent evaluation study of a PMS nurse-led project in the deprived inner-city area of Salford (in northwest England) suggests that local people perceived the service as providing a stable source of social support in an area where other sources of "social capital" and longstanding social networks were being eroded (Chapple et al 2000). After May 1997, the Labour government greatly expanded area-based initiatives aimed at regenerating deprived communities.…”
Section: The Role Of Local Communities Laypersons and Users Of Servimentioning
confidence: 99%